(untitled) (The Peerian Journal, 2022)
in the article, the author spoke about the stages of development in the nomadic peoples of Central Asia until the emergence of the first "political associations" and the emergence of statehood, the regions of residence of these tribes, the identified settlements and archaeological research on them.